Penerapan Layanan Bimbingan Kelompok dengan Menggunakan Teknik Sosiodrama untuk Mereduksi Circle Pertemanan Negatif Siswa SMA - Ahmad Saifudin; Edris Zamroni; Sucipto Sucipto (Universitas Mathla'ul Anwar Banten, 2026)
The study aimed to evaluate the implementation and effectiveness of group guidance services utilizing sociodrama techniques to mitigate negative friendship circles among students at SMA N 1 Bae Kudus. This research is novel as it specifically addresses the impact of negative friendships on adolescent development and employs sociodrama as a therapeutic intervention. The quasi-experimental design involved a one-group pretest-posttest method, revealing a significant reduction in the average score of negative friendship circles from 93.75 (high category) to 75 (medium category), indicating an 18.75% decrease. Hypothesis testing using the Wilcoxon test showed a significant difference (p = 0.018), confirming the positive effect of sociodrama techniques in enhancing students' understanding and management of their social interactions. This study provides valuable insights for educators and counselors in addressing peer relationship issues in schools.